Delusions : of grandeur, of romance, of progress : essays - David, Cazzie, 1994- (St. Martin's Press, 2026)
"In this sharp and darkly funny new essay collection from the New York Times bestselling author, Cazzie David explores the irony and existential crises of leaving youth behind. With her thirtieth birthday fast approaching, Cazzie reflects on the delusions that laid waste to her twenties and reckons with their consequences now that the specter of a new decade is looming. Touching on everything from the pressure to find the "right" partner, dealing with the relentless grip of social media, and navigating body dysmorphic spirals, Delusions cuts through the noise, offering personal anecdotes, sharp cultural criticism, and witty, honest contemplations on the chaos of contemporary adulthood. Cazzie brings her trademark voice-blunt, self-aware, and blisteringly funny-to essays that are as vulnerable as they are biting. An attempt to mature in the span of one year"-- Provided by publisher.